Correlation Between Analgesic Administration, Depression, and Knee Osteoarthritis Severity in Elderly - Gutomo, Arthur Marc; Kusumaningrum, Sulistyani; Budiningsih, Fatichati; Werdiningsih, Yulyani (Indonesian Journal of Medicine, 2025)
Background: Chronic diseases in the elderly, including osteoarthritis (OA), impact quality of life and can lead to depression. Pain caused by knee osteoarthritis may trigger stress and depression, while depression can worsen pain perception and disability. This study aimed to analyze the correlation between analgesic use, depression, and the severity of knee osteoarthritis in elderly patients. Subjects and Method: A cross-sectional study was conducted at Dr. Moewardi Hospital, Surakarta, using medical records of 99 elderly patients diagnosed with primary knee osteoarthritis between January 2018 and January 2024. Analgesic administration data were obtained from prescription records. Depression levels were assessed using the Geriatric Depression Scale (GDS), while the severity of osteoarthritis was evaluated using the Kellgren and Lawrence radiological classification. Data were analyzed using the Spearman correlation test. Results: Analgesic administration was negatively associated with depression (OR= 0.09; 95% CI= 0.03 to 0.32; p<0.001) and severity of knee OA (OR= 1.91; 95% CI= 0.60 to 6.08; p<0.001). Severity of knee OA was positively associated with depression (OR= 0.18; 95% CI= 0.05 to 0.62; p<0.001). Conclusion: Analgesic administration is negatively associated with depression and severity of knee OA. Severity of knee OA is positively associated with depression.